A Functional Single Nucleotide Polymorphism in Mucin 1, at Chromosome 1q22, Determines Susceptibility to Diffuse-Type Gastric Cancer - Saeki, Norihisa; Saito, Akira; Choi, Il Ju; Matsuo, Keitaro; Ohnami, Sumiko; Totsuka, Hirohiko; Chiku, Suenori; Kuchiba, Aya; Lee, Yeon–Su; Yoon, Kyong–Ah; Kook, Myeong–Cherl; Park, Sook Ryun; et al. (Gastroenterology (New York, N.Y. 1943), 2011)
Two major types of gastric cancer, intestinal and diffuse, develop through distinct mechanisms; the diffuse type is considered to be more influenced by genetic factors, although the mechanism is unknown. Our previous genome-wide association study associated 3 single nucleotide polymorphisms (SNPs) with diffuse-type gastric cancer (DGC); 1 was a functional SNP (rs2294008) in prostate stem cell antigen ( PSCA), but the loci of the other 2 were not investigated. We performed high-density mapping to explore a linkage disequilibrium status of the 2 SNPs at chromosome 1q22. A DGC case-control study was conducted using DNA from 606 cases and 1264 controls (all Japanese individuals) and validated using DNA from Japanese (304 cases, 1465 controls) and Korean (452 cases, 372 controls) individuals. The effects of SNPs on function were analyzed by reporter assays and analyses of splice variants. A region of a strong linkage disequilibrium with the 2 SNPs contained mucin 1 ( MUC1) and other 4 genes and SNPs significantly associated with DGC (rs2070803: P = 4.33 × 10 −13; odds ratio [OR], 1.71 by meta-analysis of the studies on the 3 panels) but not with intestinal-type gastric cancer. Functional studies demonstrated that rs4072037 ( P = 1.43 × 10 −11; OR, 1.66 by meta-analysis) in MUC1 affects promoter activity and determines the major splicing variants of MUC1 in the gastric epithelium. Individuals that carry both SNPs rs2294008 in PSCA and rs4072037 in MUC1 have a high risk for developing DGC (OR, 8.38). MUC1 is the second major DGC susceptibility gene identified. The SNPs rs2070803 and rs4072037 in MUC1 might be used to identify individuals at risk for this type of gastric cancer.